The scandal of evangelism: a biblical study of the ethics of evangelism - Thiessen, Elmer John (Cascade Books, 2018)
Introduction -- An Approach to Biblical Ethics and the Ethics of Evangelism -- Part I: Ethics of Evangelism in the New Testament -- The Gospels and Jesus -- Acts and the Apostles Paul's Epistles -- General Epistles and Revelation -- Summary of Biblical Analysis: Guidelines for Ethical Evangelism -- Part II: Applied Topics -- Evangelism of Children -- Evangelism in Professional Life: The Academy -- Evangelism and Humanitarian Aid --Ethics of Proselytism -- Conclusion